Kesenjangan Gender Bidang Pendidikan Ditinjau dari Aspek Kebijakan di Kota Semarang - Redjeki, S. Sri (Jurnal Civicus, 2008)
Kesenjangan Gender Bidang Pendidikan Ditinjau dari Aspek Kebijakan di Kota Semarang